1991
DOI: 10.1111/j.1151-2916.1991.tb06861.x
|View full text |Cite
|
Sign up to set email alerts
|

Precoarsening to Improve Microstructure and Sintering of Powder Compacts

Abstract: MgO and Al2O3 were sintered by two types of processes: a conventional isothermal sintering and a two-step sintering consisting of a n initial low-temperature precoarsening treatment before conventional isothermal sintering. The final microstructure from two-step sintering can be more uniform and finer than that of compacts sintered conventionally. A narrow-size-distribution a l u m i n a powder was sintered under constant-heating-rate conditions, with and without a precoarsening treatment, and the results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 14 publications
2
44
1
1
Order By: Relevance
“…A direct consequence of the rate-controlled sintering method is fast firing (Harmer & Brook, 1981), which can produce dense materials with small grain size, minimizing the time of exposure at temperatures where grain growth is fast compared with densification (Chu et al, 1991). This is possible because, generally, coalescence mechanisms (eg, surface diffusion and vapor transport) prevail over densification mechanisms (eg, volumetric diffusion by grain boundary diffusion) at low temperatures.…”
Section: Effect Of Heating Curve In the Sinteringmentioning
confidence: 99%
See 4 more Smart Citations
“…A direct consequence of the rate-controlled sintering method is fast firing (Harmer & Brook, 1981), which can produce dense materials with small grain size, minimizing the time of exposure at temperatures where grain growth is fast compared with densification (Chu et al, 1991). This is possible because, generally, coalescence mechanisms (eg, surface diffusion and vapor transport) prevail over densification mechanisms (eg, volumetric diffusion by grain boundary diffusion) at low temperatures.…”
Section: Effect Of Heating Curve In the Sinteringmentioning
confidence: 99%
“…De Jonghe et al (Chu et al, 1991;Lin & DeJonghe, 1997a, 1997b found that pre-heat treatment (50 to 100 hours) at low temperatures (800 ºC), in which little or no densification occurs, can improve densification and microstructure of a high purity alumina with and without MgO addition. A consequence of these pre-treatments was reducing the densification rate in the initial stages of sintering.…”
Section: Effect Of Heating Curve In the Sinteringmentioning
confidence: 99%
See 3 more Smart Citations